2006
DOI: 10.5424/sjar/2006041-179
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated hydraulic conductivity of disturbed and undisturbed loam soil

Abstract: The soil water content-pressure head curve [q(h)], described by van Genuchten, was used to predict some hydraulic characteristics of a Xeric torriorthent soil. Experimental data of volumetric soil water content (q) and pressure head (h) were adjusted to the model, obtaining the three independent parameters used to calculate the unsaturated soil hydraulic conductivity (K) and soil water diffusivity (D). The K(q) functions for disturbed and undisturbed soil samples were statistically different pointing to the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
1
3
0
1
Order By: Relevance
“…High correlation and significant factor loadings of SMC and Ks in the principal components of the hydro-meteorological and soil parameters indicated that SMC was highly influenced by the existing Ks of the soil. This was consistent with other studies that reported a positive effect of Ks on SMC (Abrisqueta et al, 2006;Schuhmann et al, 2011). Our study found that SMC and Ksat were poorly correlated, indicating that SMC is weakly associated with Ksat when the soil is saturated.…”
Section: Relationships Amongst the Hydro-meteorological And Soil Parasupporting
confidence: 93%
“…High correlation and significant factor loadings of SMC and Ks in the principal components of the hydro-meteorological and soil parameters indicated that SMC was highly influenced by the existing Ks of the soil. This was consistent with other studies that reported a positive effect of Ks on SMC (Abrisqueta et al, 2006;Schuhmann et al, 2011). Our study found that SMC and Ksat were poorly correlated, indicating that SMC is weakly associated with Ksat when the soil is saturated.…”
Section: Relationships Amongst the Hydro-meteorological And Soil Parasupporting
confidence: 93%
“…Al-Taie (2005) [4] found that 45 days is sufficient for equilibrium to occur for most types of soil. Table (1) lists the saturated solutions used in this method and it's relative humidity and matric suction.…”
Section: Test Programmementioning
confidence: 99%
“…All the parameters that influence the soil-water characteristic curve behaviour also influence the unsaturated coefficients stated above [18]. One of the most factors that influence the soil water characteristic curve and unsaturated coefficients of permeability and diffusion is the anisotropy [1], which has been studied in this research paper.…”
Section: Introductionmentioning
confidence: 99%
“…It also plays a dominant role in predictions of water content profiles in concrete during wetting and drying conditions, in the context of forecasting the service life of concrete structures (Pradhana et al 2005, Das andKondraivendhan 2012, andreferences therein). But hydrology is the branch of scientific knowledge where hydraulic diffusivity is more extensively used, namely for prediction of natural fluid flow through rock masses (Li 1984, Delépine et al 2004, Pacheco and Alencoão 2006, Pacheco and Van der Weijden 2012, soil horizons (Appoloni et al 1990, Chen 1998, Abrisqueta et al 2006 or aquifer sediments, also known as porous media. The literature on methods for assessing hydraulic diffusivity of porous media aquifers is vast.…”
Section: Introductionmentioning
confidence: 99%